Prenatal ultrasound parameters in single-suture craniosynostosis. (3rd August 2018) - Cornelissen, Martijn J.; Apon, Inge; van der Meulen, Jacques J. N. M.; Groenenberg, Irene A. L.; Kraan – van der Est, Mieke N.; Mathijssen, Irene M. J.; Bonsel, Gouke J.; Cohen – Overbeek, Titia E.
Abstract: Introduction: Although single-suture craniosynostosis is diagnosed sporadically during pregnancy, timely referral is critical for its treatment. Additionally, craniosynostosis leads to increased maternofetal trauma during birth. In the Netherlands, 95% of pregnant women receive a standard ultrasound at around 20 weeks of gestation, potentially an ideal setting for detecting craniosynostosis prenatally. To enhance the prenatal detection of the metopic and the sagittal suture synostosis, we wished to identify new screening parameters. Materials and methods: We retrospectively analyzed data of the 20-week anomaly scan in trigonocephaly patients ( n  = 41), scaphocephaly patients ( n  = 41), and matched controls ( n  = 82). We measured six different cranial dimensions, including head circumference, biparietal diameter, and occipito-frontal diameter, defining the cephalic index as the ratio between biparietal and occipito-frontal diameter. Results: Prenatal biometric measurements did not differ significantly between trigonocephaly patients and controls. Although significantly lower in scaphocephaly patients (0.76 versus 0.79; p  = .000), the cephalic index by itself is not appropriate for screening at 20 weeks of gestation. Longitudinal analysis suggests that a deflection in BPD curve is found in scaphocephaly patients, starting at 20 weeks of gestation. Conclusions: Prenatal biometric measurements do not differ significantly between trigonocephaly patients and controls. The CI is lower in scaphocephaly patients. A deflection in BPD curve should be followed by 3 D imaging of the cranial sutures.